First-principles study of structural, elastic, electronic and optical properties of XRbCl3 (X = Ca, Ba) perovskite compounds - Norah Algethami; Aiman Jehan; Nasir Rahman; Saima Naz Khan; Wafa Mohammed Almalki; Mudasser Husain; Vineet Tirth; Hanan A. Althobaiti; Yazen M. Alawaideh; Khamael M. Abualnaja; Ghaida Alosaimi (Results in Physics)
We report on DFT calculations of electronic, elastic and optical properties of XRbCl3 (X = Ca, Ba) perovskites using the FP-LAPW method. The investigated compounds crystallize in a cubic structure, with structural optimization performed using the Birch-Murnaghan equation of state. The optimized lattice parameters were determined to be 5.83 Å and 5.77 Å for XRbCl3 (X = Ca, Ba), respectively. The elastic properties, including cubic elastic constants, Poisson’s ratio (ν), elastic moduli, anisotropy factor, and Pugh’s ratio (B/G), were computed using the highly precise IRelast package integrated within the WIEN2k software. The analysis confirms that these materials exhibit mechanical stability, ductility, and elastic anisotropy. The electronic band structures of CaRbCl3 and BaRbCl3 were accurately determined using DFT calculations with the TB-mBJ approximation, revealing direct band gaps of 1.51 eV and 2.76 eV, respectively, at the Γ-Γ high-symmetry points. The optical properties, including the absorption coefficient, refractive index n(ω), reflectivity, and optical conductivity, were analyzed within the energy range of 0–15 eV, offering valuable insights into their response to varying photon energies. The favorable optical characteristics of these compounds highlight their potential for advancements in light-based technologies and energy-related applications.